Doing theology basic ecclesial communities in the Philippines : a new way of being church in the Philippines - Gabriel, Manuel G. (Pasig City Anvil, 2008)
"The reflections on the BCC/BEC experiences presented in this book have covered thirty-six years of pastoral ministry, all inspired by a Vatican II concept of the Church being a communion-in-mission. The articles have enabled us to journey through six dioceses of the Metro Manila area and the national consultations on BECs. In the process, they have unraveled the varied settings and contexts where BECs can be tried as a new way of being church, a way to evangelize the unchurched and unevangelized in the Philippines."--Epilogue.
Foreword : theological reflection on BECs in the Philippines / by Luis Antonio Tagle -- Preface -- Acknowledgment -- Basic Christian communities : the Fatima experience -- Basic Christian communities : the University of the Philippines experience -- Patterns from the journeys of a decade -- A reflection on the Inter-BCC Dialogue : a Philippine experience -- Lay involvement in the BECs in the Philippine setting : reality and challenges -- Inculturation from a pastor's point of view -- Basic ecclesial communities in the Philippines : some missiological challenges -- Basic ecclesial communities in the Philippines : some missiological perspectives -- A pastoral approach to the sustainability of BECs in the light of culture -- A modular design for parish pastoral planning in building BCCs -- The application of new evangelization and BEC to Saint Paul Sisters' ministries -- The indispensability of theology in pastoral ministry : on doing theology and BECs -- Epilogue.
Keywords: Basic Christian communities -- Philippines; Christian communities -- Catholic Church; Theology -- Philippines